Cloud point Extraction Of Methimazole By Direct (UV- Vis Spectrophotometer) And Indirect (Flame Atomic Absorption) methods - Hasan, Sawsan Askar; Shakkor, Shahla Jamal (South Eastern European Journal of Public Health, 2024)
Abstract A new technique based on the formation of a chelate Methimazole-Fe(III) at 400 nm was used for the determination of Methimazole 114 as a surfactant in some pharmaceuticals using indirect flame atomic absorption spectroscopy (FAAS) and UV-visible methods based on Triton turbidity extraction. The optimal turbidity extraction temperature was 75.0°C after 25 min of extraction of the complex [MET-Fe(III)] with ethanol. The structure of the Methimazole-Fe(III) chelate was determined by the molar ratio method. A 1:1 L:M (ligand:metal) ratio was produced. The Beer law was employed in the concentration range of 2.5-30 and 2.5-32.5 g/mL for the UV and FAAS, respectively.. The limits of detection (LOD) and quantification (LOQ) were (0.3784) g/ml and (1.2612) g/ml, respectively, for these techniques. The technique has been approved and successfully used in the production of pharmaceutical preparations such as: B. Methimazole capsules sold in Iraq. The analytical results were validated by statistical and recycling studies with satisfactory results.